O problema da unidade da razão em Kant - Perin, Adriano (2006)
This master thesis presents a reconstruction of the problem of the unity of reason in Kant s critical-transcendental philosophy. Bearing in mind that there is much disagreement in the literature, not only as to the critical answer to this problem, but also as to its specificity and systematic function within the various moments in which it is considered by Kant, this approach centers essentially on Kant s own argumentation. The aim of this research is to show that Kant s treatment of the problem follows the development of the critical-transcendental philosophy and that it can only be understood insofar as this development is presented. Therefore, a search for the systematic localization of the moments in which Kant approaches the problem of the unity of reason has been carried out, with the intention of justifying that this approach is fundamentally connected with the critical intention of establishing the boundaries that guarantee legitimacy to reason and assure its authenticity to operate in the theoretical as well as in the practical domain. The investigation is guided by the necessity to understand that both the negative results at which Kant arrives in the search of the demonstration of the unity of reason and the only critical answer admitted to this problem have their genesis in the systematic possibilities considered by the critical philosophy as a whole. Initially, in view of the argumentation that corresponds to the first period of this philosophy, an examination of Kant s search for a solution to the problem of the unity of reason from the theoretical use is carried out. Secondly, the systematic identification of the impossibility of solving the problem through this route leads to the consideration of an effort to establish the unity from the practical use and, likewise, to the discovery that the theoretical and practical uses of reason must be legitimized in two distinct domains of reason and, thus, the unity of reason cannot be guaranteed from either of its uses. Finally, faced with this situation, an exploration of the answer guaranteed to the problem of the unity of reason by the Kantian argumentation that considers the relation of the theoretical and practical domains in a regulative manner is carried out. As a result of the systematic impossibility to establish the unity of reason from one of its uses, the necessary self-sufficient validation of these uses, and, also, the fact that the relation of their domains can only be admitted as regulative, the conclusion reached is that the unity of reason is a fundamental presupposition of the critical philosophy in the articulation of its entirety, but that the critical answer to this problem consists in the justification of the impossibility of its demonstration.